MANAJEMEN STRATEGI : Perempuan dan Kewirausahaan Berkelanjutan - S.E., M.M, Dr. Monalisa,; S.E., MBA, Dr. Elia Ardyan,; Mustikarini, S.E., M.Sc, Dr. Carolina Novi; Tanesia, S.E., MBA, Cindy Yoel; S.E., M.M, Asriah Syam, (Lajagoe Pustaka, 2024)
Selamat datang dalam buku ini yang berjudul